2011
DOI: 10.1007/s10545-011-9382-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ATP synthase: architecture, function and pathology

Abstract: Human mitochondrial (mt) ATP synthase, or complex V consists of two functional domains: F1, situated in the mitochondrial matrix, and Fo, located in the inner mitochondrial membrane. Complex V uses the energy created by the proton electrochemical gradient to phosphorylate ADP to ATP. This review covers the architecture, function and assembly of complex V. The role of complex V di-and oligomerization and its relation with mitochondrial morphology is discussed. Finally, pathology related to complex V deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
367
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(380 citation statements)
references
References 150 publications
3
367
0
10
Order By: Relevance
“…Complex V phosphorylates ADP to produce ATP by utilizing the electrochemical gradient produced during CI to CIV electron transfer [90].…”
Section: Oxphos Complex Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex V phosphorylates ADP to produce ATP by utilizing the electrochemical gradient produced during CI to CIV electron transfer [90].…”
Section: Oxphos Complex Vmentioning
confidence: 99%
“…Pathogenic mutations to MTATP6 [92] can result in maternally inherited Leigh syndrome (MILS) [93] and neuropathy, ataxia, retinal pigmentosa (NARP) [90,92]. Additionally, mutations to CV assembly factors, TMEM70 [94] and ATPAF2 [95] have been identified and present with cardiomyopathy, hypotonia, intrauterine growth restriction and oligohydramnios [94,95] (Table 1).…”
Section: Oxphos Complex Vmentioning
confidence: 99%
“…[2] At micromolar concentrations 1 inhibited F 0 F 1 -ATPase by binding with subunit F 0 and blocking OSCP (oligomycin sensitivity conferring protein). [3] Previously a series of modifications at the side chain and chemical transformation of the lactone moiety of 1 have been developed. [4][5][6][7][8] However, all derivatives modificated at the lactone moiety were less potent than 1.…”
Section: Corresponding Author E-mail: Shchekotikhin@mailrumentioning
confidence: 99%
“…Two previous publications suggested that ATP5B might be involved in mitochondrial dynamics. Wang et al demonstrated that small molecule M1 promotes the mitochondrial fusion by increasing ATP5A/B (Wang et al 2012) and Jonckheere et al have reported mitochondrial fragmentation and dysfunction from a mitochondrial complex V (ATP5B included) deficient mutations in patient fibroblasts (Jonckheere et al 2011;Jonckheere et al 2012). Such changes in mitochondrial shape have been shown to directly impact cell differentiation and proliferation (Ahn & Metallo 2015); however, little is known as to how ATP5B regulates the phenotype and metabolic characteristics of mitochondria.…”
Section: Introductionmentioning
confidence: 99%